Public education finance systems in the United States and funding policies for populations with special educational needs. - Verstegen, Deborah A (Education Policy Analysis Archives, 2011)
This research investigates state finance policies for public education using survey methodology. The purpose is to update previous work and the existing knowledge base in the field as well as to provide a compendium of finance and policy options that are used across the states to finance public elementary and secondary schools. Chief state school officers or their designee were queried; data were provided for all 50 states and posted on the web for verification. This article presents the findings together with crosscutting themes including major state apportionment policies for K-12, special student populations, capital outlay provisions and transportation funding.